Unpublished Manuscripts from 1951 to 2007 - Hörmander, Lars (Springer International Publishing, 2018)
This book presents, for the first time, the unpublished manuscripts of Lars Hörmander, written between 1951 and 2007. Hörmander himself organised the manuscripts and also wrote the notes explaining their origins, presenting the material in the form he fully intended it to be published in. As his daughter, Sofia Broström, mentions in the Foreword, towards the end of his life, Hörmander "carefully went through his unpublished manuscripts, checking and revising each of them with his very critical eye, deciding what should be kept for posterity and what should be thrown out". He also compiled the complete bibliography of all his published mathematical works that is included at the end of the present book. Of both historical and mathematical value, the contents of this book will undoubtedly inspire mathematicians of different horizons.